Tinjauan Yuridis terhadap Pertimbangan Majelis Hakim dalam Memutus Perkara Pidana Persetubuhan Anak: (STUDI : Putusan N0. 80/PID.SUS/2023/PN KPG) - Jafrai Musa Robo; Heryanto Amalo; Debi F. Ng. Fallo (Badan Penerbit STIEPARI Press, 2025)
A child is defined as a person who is not yet an adult or a person who is still under the supervision of a parent or guardian. In Indonesia, regulations regarding child protection have been issued according to the needs of the community. One of the sexual violence that occurred in Sabu Raijua Regency was the crime of sexual intercourse with a child, namely in Decision Number 80/pid.sus/2023/PN Kupang. The threat of criminal penalties for perpetrators of the crime of sexual intercourse with a child has been regulated in Law Number 35 of 2014 concerning amendments to Law Number 23 of 2002 concerning Child Protection. This research method uses normative legal research which is carried out by examining primary legal materials, secondary legal materials, and tertiary legal materials. The legal material collection technique used is library research. Based on the results of the research and discussion, that the basis for the consideration of the panel of judges in deciding the criminal case of child sexual intercourse (study: decision No.80/pid.sus/2023/PN Kpg is by considering legal and non-legal considerations. legal considerations are the indictment of the public prosecutor, the demands of the public prosecutor, the testimony of the victim's witness, the instructions and the testimony of the defendant. and non-legal considerations are seen from the psychological, philosophical, sociological aspects and the Circular of the Supreme Court No. 1 of 2017 concerning the Enforcement Formulation of the Results of the Supreme Court Chamber Plenary Session as a guideline for implementing tasks for the Court regarding the imposition of minimum sentences on perpetrators of child and adult crimes but the victims are children.